Grafting of Chloroacetic Acid on EGDE Cross-Linked Chitosan to Enhance Stability and Adsorption Capacity For Pb(II) Ions - Abu Masykur; Sri Juari Santosa; Dwi Siswanta; Jumina Jumina (Indonesian Journal of Chemistry, 2014)
The aims of this research is to synthesize a chitosan derivative insoluble in acidic aqueous medium and that has high adsorption capacity for Pb(II) ions by cross-linking and grafting. Cross-linking and grafting were done using ethylene glycol diglycidyl ether (EGDE) and chloroacetic acid, respectively. The modified chitosan was characterized using FTIR spectrophotometer, XRD and TG-DTA. Chitosan and Chit-EGDE-Acetate was applied as adsorbent of Pb(II) ions in a batch system. The concentration of Pb(II) in adsorption medium was quantified using AAS. The result showed that the adsorption was optimum at pH 5, contact time of 200 min for chitosan and 300 min for Chit-EGDE-Acetate. Adsorption of Pb(II) ions on both adsorbents followed pseudo second order kinetic equation. Adsorption of Pb(II) ions on chitosan followed Freundlich isotherm while that on Chit-EGDE-Acetate followed the Langmuir adsorption isotherm. The adsorption capacity of Chit-EGDE-Acetate for Pb(II) ions was 200.0 mg L-1 while that for chitosan was 166.7 mg L-1. Interaction type of Pb(II) ions on adsorbent was determined by sequential desorption.